2020
DOI: 10.1186/s12931-020-01414-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling reveals disease-specific characteristics of epithelial cells in idiopathic pulmonary fibrosis

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is an incurable disease characterized by progressive lung fibrosis ultimately resulting in respiratory failure and death. Recurrent micro-injuries to the alveolar epithelium and aberrant alveolar wound healing with impaired re-epithelialization define the initial steps of the pathogenic trajectory. Failure of timely alveolar epithelial repair triggers hyper-proliferation of mesenchymal cells accompanied by increased deposition of extracellular matrix into the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Recently, it has become apparent that epithelial remodelling is a key driver of IPF; however, the underlying mechanisms remain unclear (Boesch et al , 2020 ; Habermann et al , 2020 ; Selman & Pardo, 2020 ). Therefore, we focused on unveiling the pathological drivers of aberrant lung epithelial remodelling and its fibrotic consequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has become apparent that epithelial remodelling is a key driver of IPF; however, the underlying mechanisms remain unclear (Boesch et al , 2020 ; Habermann et al , 2020 ; Selman & Pardo, 2020 ). Therefore, we focused on unveiling the pathological drivers of aberrant lung epithelial remodelling and its fibrotic consequences.…”
Section: Resultsmentioning
confidence: 99%
“…We observed an induction of aSMA levels in substituted MCs (i), consistent with injured epithelial-driven fibroblast-to-myofibroblast transition (FMT). Accordingly, replacement with untreated AECs (ii) or a combination of fresh media and MCs (iii) decreased aSMA expression in MCs (Fig 1G Recently, it has become apparent that epithelial remodelling is a key driver of IPF; however, the underlying mechanisms remain unclear (Boesch et al, 2020;Habermann et al, 2020;Selman & Pardo, 2020). Therefore, we focused on unveiling the pathological drivers of aberrant lung epithelial remodelling and its fibrotic consequences.…”
Section: Injured Epithelial Cells Activate a Fibrotic Cascade With Me...mentioning
confidence: 99%
“…Although, our models may not fully reflect the in vivo situation of IPF HC, they appear superior to previously used models (22, 25) as BC, used in this study, 1) are IPF patient-derived and 2) were isolated from fibrotic IPF parenchyma, and not from the airways. Using cells from patient-derived tissue and from the region of interest seems important as it was shown that cells maintain disease- and region-specific characteristics when cultured in vitro (27, 28). Although our current study does not provide new insights into the origin or function of alveolar BC in IPF, the use of the here presented models in future studies will greatly enhance our knowledge about the role of alveolar BC in HC formation and its potential pharmacological inhibition in IPF.…”
Section: Discussionmentioning
confidence: 99%
“…Primary lung-resident MSCs can be isolated from patients with idiopathic pulmonary fibrosis (IPF), a progressive lung disease of unknown etiology, and the increased number of MSCs accompanied by the augmented ECM deposition has been observed in the lung interstitium ( Hostettler et al, 2017 ; Boesch et al, 2020 ). Lung-resident MSCs have been also shown to undergo phenotype conversion, for example, to myofibroblasts in vivo , and to increase ECM products contributing to pulmonary fibrogenesis ( Chen et al, 2018 ; Cao et al, 2020 ).…”
Section: Mesenchymal Stem/stromal Cells In Contribution To Progressiv...mentioning
confidence: 99%